Treatment of obesity with thyroid hormones in Europe: data from the THESIS* Collaboration - Galofré, Juan C.; Díez, J. J.; Attanasio, Roberto; Nagy, E. V.; Negro, R.; Papini, Enrico; Perros, P.; Žarković, M.; Akarsu, E.; Alevizaki, M.; Ayvaz, G.; Bednarczuk, T.; et al. (Journal of endocrinological investigation, 2024)
The use of thyroid hormones (TH) to treat obesity is unsupported by evidence as reflected in international guidelines. We explored views about this practice, and associations with respondent characteristics among European thyroid specialists.
Online veröffentlicht: 5. Juni 2024
Gesehen am 25.11.2024